Reliabilitas dan validitas Self-Compassion Scale versi Bahasa Indonesia - Sugianto, Dicky; Suwartono, Christiany; Sutanto, Sandra Handayani (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
Self-compassion is a healthy attitude toward oneself which positively associated to an individual’s mental health. Self-Compassion Scale (SCS) is a common instrument to measure levels of self-compassion However, to date, there is no study that evaluates the psychometric properties of the Indonesian version of SCS. This study aims to adapt the SCS into Indonesian language and to evaluate the psychometric properties of the Indonesian version of SCS. Participants in this study were 329 college students enrolled in universities in Jakarta and surrounding areas and were recruited through convenience sampling. Instrument used in this research is the Indonesian version of SCS, which we named Skala Welas Diri (SWD). The result of psychometric evaluation using confirmatory factor analysis (CFA), construct validity, and Cronbach’s Alpha coefficient showed good validity and reliability of SWD. The study suggested that SWD have a similar theoretical model as SCS. The study concludes that SWD could be used as an adequate measurement of self-compassion.